Blood lipids and lipoproteins in child and adolescent athletes - Eisenmann, J. C. (Sports Medicine, 2002)
The purpose of this review is to describe the age- and gender-associated variation in blood lipids of young athletes and examine the association between training status, peak oxygen consumption (V-dot(2peak)), and body fatness with blood lipids in young athletes. Results from cross-sectional studies suggest similar levels of total cholesterol (TC), lower levels of triglycerides (TG) and low-density lipoprotein-cholesterol (LDL-C), and higher levels of high-density lipoprotein-cholesterol (HDL-C) in young athletes compared with controls. Longitudinal data show that the age- and gender-associated variation in blood lipids in young distance runners is similar to youth in the general population; TC and LDL-C remain stable, HDL-C declines during adolescence (especially in males), and TG increases with age. Considerable heterogeneity exists in the blood lipids of young athletes, including dyslipidaemic values. Age, sexual maturity status, training status, V-dot(2peak) and body fatness are determinants of blood lipids in young athletes. V-dot(2peak) is a significant predictor of HDL-C independent of body fatness. Further research is warranted to examine: the prevalence rates of dyslipidaemia in various sport groups; andthe complex interactions of genes, biological maturation, exercise training, dietary intake and composition, skeletal muscle and adipose tissue properties on lipoprotein metabolism in young athletes.